Gambaran Tingkat Pengetahuan Siswa tentang Pertolongan Pertama pada Kecelakaan di Sekolah Menengah Atas - Ni Kadek Pon Widiastuti; I Made Sudarma Adiputra (Jurnal Akademika Baiturrahim Jambi, 2022)
Injuries are still an important issue that must be discussed. An accident is an unwanted or unexpected event that can cause injury and even fatalities. In Indonesia, there was an increase in the incidence of injuries by 9.2% from 2013-2018. Denpasar is the city with the most frequent injury rates in the province of Bali, with a total of 4,450 accidents in 2018, adolescents with an age range of 15-24 years being the age most frequently involved in accidents. Efforts are being made to prevent injury deaths. is the promotion of health, teachers are the key in education in schools. First Aid in Accidents is an action needed in various emergencies, both at school, at home, and on the road. The purpose of this study was to identify the level of knowledge of students about first aid in accidents at Santo Yoseph Catholic High School Denpasar. This study uses a descriptive method, with a quantitative approach to 193 samples using a quota sampling technique. The instrument used was a questionnaire on the level of students' knowledge of first aid in an accident, totaling 28 statement items. The research questionnaire has been tested for validity and reliability at SMA Dharma Praja Denpasar, declared valid and reliable. The results of the study based on the age characteristics of the respondents, most of the respondents were 16 years old as many as 103 respondents (53.4%), based on gender, most of the respondents were female (115 respondents (59.6%). Identification of the level of knowledge obtained some samples. have a "good" level of knowledge as many as 151 respondents (78.2%), then the category of sufficient knowledge is 42 respondents (21.8%), and there are no students who have less knowledge.